2022
DOI: 10.1002/bte2.20220048
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing surface‐to‐bulk stability of layered Co‐free Ni‐rich cathodes for long‐life Li‐ion batteries

Abstract: Layered Co‐free Ni‐rich cathodes are the most cost‐effective for high‐energy‐density Li‐ion batteries (LIBs), yet the structural instability and interfacial side reactions seriously hamper their commercial applications versus the Co‐contained counterpart. Herein, a synchronous Ge‐doping and Li4GeO4‐coating of the Co‐free Ni‐rich cathodes have been realized to tackle these limitations during high‐temperature lithiation of the corresponding hydroxide precursors. The nonmagnetic Ge4+ doping effectively relieves t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…1d), and its structural renement demonstrated that BA-NCM85 had an extremely low Li/Ni mixed value of 1.55%. 29,30 Furthermore, the Li/Ni cation disorder of B-NCM85 (1.83%) and A-NCM85 (2.26%) was much lower than that of pristine NCM85 (3.21%) (Fig. S6 †).…”
Section: Resultsmentioning
confidence: 98%
“…1d), and its structural renement demonstrated that BA-NCM85 had an extremely low Li/Ni mixed value of 1.55%. 29,30 Furthermore, the Li/Ni cation disorder of B-NCM85 (1.83%) and A-NCM85 (2.26%) was much lower than that of pristine NCM85 (3.21%) (Fig. S6 †).…”
Section: Resultsmentioning
confidence: 98%
“…The Ni 0.9 Mn 0.1 (OH) 2 precursors were prepared by a co-precipitation method in a batch reactor (10 L) under an argon atmosphere, which has been described in detail in our previous works. 10 The obtained Ni 0.9 Mn 0.1 (OH) 2 precursor was mixed with stoichiometric LiOH•H 2 O (molar ratio of lithium to transition metals = 1.02). The mixture was precalcined at 450 °C for 6 h followed by sintering at 770 °C for 13 h in a pure oxygen atmosphere to obtain the pristine LiNi 0.9 Mn 0.1 O 2 oxides (NM91).…”
Section: Methodsmentioning
confidence: 99%
“…There are two main methods available. One is to coat a layer of inorganic compounds on the cathodes as a physical barrier to prevent the erosion of the active materials by adverse components such as HF in the electrolyte. , However, its low ductility makes it easy to crack and fall off after long-term cycles owing to the repeated volumetric shrinkage and swelling of cathodes . The interfacial contact resistances among the cathode, coating layer, and CEI film also gradually increase, vastly worsening the rate performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[24][25][26][27][28][29][30][31] Additionally, anion substitution, 32 partial nickel substitution in LiNiO 2 with various elements such as Mg, Mn, Cr, Fe, Co, Al, Ga, Zr, Ti, Sb, W, Mo, and F, has been explored. [33][34][35][36][37]50,51 Concurrent coating techniques, 38,39 surface-tobulk modications, 40,41 core/shell-type structure design, 42,43 and innovative recycling methodologies 44 for Ni-rich compounds also contribute to this growing eld. These developments have reignited interest across academia and industry, as most of these observations demonstrate improved cyclic stability and rate capability.…”
mentioning
confidence: 99%